Interleukin-34 and immune checkpoint inhibitors: Unified weapons against cancer - Alshaebi, Fadhl; Safi, Mohammed; Algabri, Yousif A.; Al-Azab, Mahmoud; Aldanakh, Abdullah; Alradhi, Mohammed; Reem, Alariqi; Zhang, Caiqing (Frontiers in Oncology, 2023)
Interleukin-34 (IL-34) is a cytokine that is involved in the regulation of immune cells, including macrophages, in the tumor microenvironment (TME). Macrophages are a type of immune cell that can be found in large numbers within the TME and have been shown to have a role in the suppression of immune responses in cancer. This mmune suppression can contribute to cancer development and tumors’ ability to evade the immune system. Immune checkpoint inhibitors (ICIs) are a type of cancer treatment that target proteins on immune cells that act as “checkpoints,” regulating the activity of the immune system. Examples of these proteins include programmed cell death protein 1 (PD-1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4). ICIs work by blocking the activity of these proteins, allowing the immune system to mount a stronger response against cancer cells. The combination of IL-34 inhibition with ICIs has been proposed as a potential treatment option for cancer due to the role of IL-34 in the TME and its potential involvement in resistance to ICIs. Inhibiting the activity of IL-34 or targeting its signaling pathways may help to overcome resistance to ICIs and improve the effectiveness of these therapies. This review summarizes the current state of knowledge concerning the involvement of IL-34-mediated regulation of TME and the promotion of ICI resistance. Besides, this work may shed light on whether targeting IL-34 might be exploited as a potential treatment option for cancer patients in the future. However, further research is needed to fully understand the mechanisms underlying the role of IL-34 in TME and to determine the safety and efficacy of this approach in cancer patients.